Analisis Penyerapan Tenaga Kerja Industri Sedang dan Besar di Kabupaten Jepara Tahun 2001-2022 - Pratama, Muhammad Aria Restihani; Arif, Muhammad (Jurnal EMT KITA, 2024)
Absorption of labor is one of the crucial things in a region, with the presence of labor the unemployment rate in the region can be reduced and this will in itself help to increase economic development. This research aims to analyze the influence of the district minimum wage, population, number of GRDP industries in the industrial sector, education level, and export value. The analytical method used is a quantitative method with ECM data regression. The results of this research show that in the short term labor absorption in Jepara Regency in 2001-2022 is influenced by population and number of industries, while in the long term, it is only influenced by the number of industries.